Spatial differences in subsidence and relative sea-level rise in the Netherlands during the Holocene - Kim de Wit; Kim M. Cohen; Roderik S.W. van de Wal (Global and Planetary Change, 2026)

The acceleration of sea-level rise along the coast of the Netherlands started in the 1960s - Iris Keizer; Dewi Le Bars; Cees de Valk; André Jüling; Roderik van de Wal; Sybren Drijfhout (Ocean Science, 2023)
The global acceleration of sea-level rise (SLR) during the 20th century is now established. On the local scale, this is harder to establish as several drivers of SLR play a role, which can mask the acceleration. Here, we study the rate of SLR along the coast of the Netherlands from the average of six tide gauge records covering the period 1890–2021. To isolate the effects of the wind field variations and the nodal tide from the local sea-level trend, we use four generalised additive models (GAMs) which include different predictive variables. From the sea-level trend estimates, we obtain the continuous evolution of the rate of SLR and its uncertainty over the observational period. The standard error in the estimation of the rate of SLR is reduced when we account for nodal-tide effects and is reduced further when we also account for the wind effects, meaning these provide better estimates of the rate of SLR. A part of the long-term SLR is due to wind forcing related to a strengthening and northward shift of the jet stream, but this SLR contribution decelerated over the observational period. Additionally, we detect wind-forced sea-level variability on multidecadal timescales with an amplitude of around 1 cm. Using a coherence analysis, we identify both the North Atlantic Oscillation and the Atlantic Multidecadal Variability as its drivers. Crucially, accounting for the nodal-tide and wind effects changes the estimated rate of SLR, unmasking an SLR acceleration that started in the 1960s. Our best-fitting GAM, which accounts for nodal and wind effects, yields a rate of SLR of about 1.72.21.3 mm yr−1 in 1900–1919 and 1.51.91.2 mm yr−1 in 1940–1959 compared to 2.93.52.4 mm yr−1 in 2000–2019 (where the lower and upper bounds denote the 5th and 95th percentiles). If we discount the nodal tide, wind and fluctuation effects and assume a constant rate of SLR, then the probability (p value) of finding a rate difference between 1940–1959 and 2000–2019 of at least our estimate is smaller than 1 %. Consistent with global observations and the expectations based on the physics of global warming, our results show unequivocally that SLR along the Dutch coast has accelerated since the 1960s.

Editorial: Climate Services for Adaptation to Sea-Level Rise - Gonéri Le Cozannet; Robert James Nicholls; Roderik van de Wal; Michael Dylan Sparrow; Jing Li; Julie Billy (Frontiers in Marine Science, 2022)

Correction to: Concepts and Terminology for Sea Level: Mean, Variability and Change, Both Local and Global - Jonathan M. Gregory; Stephen M. Griffies; Chris W. Hughes; Jason A. Lowe; John A. Church; Ichiro Fukumori; Natalya Gomez; Robert E. Kopp; Felix Landerer; Gonéri Le Cozannet; Rui M. Ponte; Detlef Stammer; et al. (Surveys in Geophysics, 2019)

Concepts and Terminology for Sea Level: Mean, Variability and Change, Both Local and Global - Jonathan M. Gregory; Stephen M. Griffies; Chris W. Hughes; Jason A. Lowe; John A. Church; Ichiro Fukimori; Natalya Gomez; Robert E. Kopp; Felix Landerer; Gonéri Le Cozannet; Rui M. Ponte; Detlef Stammer; et al. (Surveys in Geophysics, 2019)

Recent Progress in Greenland Ice Sheet Modelling - Heiko Goelzer; Alexander Robinson; Helene Seroussi; Roderik S.W. van de Wal (Current Climate Change Reports, 2017)

Sea Level Change and Coastal Climate Services: The Way Forward - Gonéri Le Cozannet; Robert Nicholls; Jochen Hinkel; William Sweet; Kathleen McInnes; Roderik Van de Wal; Aimée Slangen; Jason Lowe; Kathleen White (Journal of Marine Science and Engineering, 2017)
For many climate change impacts such as drought and heat waves, global and national frameworks for climate services are providing ever more critical support to adaptation activities. Coastal zones are especially in need of climate services for adaptation, as they are increasingly threatened by sea level rise and its impacts, such as submergence, flooding, shoreline erosion, salinization and wetland change. In this paper, we examine how annual to multi-decadal sea level projections can be used within coastal climate services (CCS). To this end, we review the current state-of-the art of coastal climate services in the US, Australia and France, and identify lessons learned. More broadly, we also review current barriers in the development of CCS, and identify research and development efforts for overcoming barriers and facilitating their continued growth. The latter includes: (1) research in the field of sea level, coastal and adaptation science and (2) cross-cutting research in the area of user interactions, decision making, propagation of uncertainties and overall service architecture design. We suggest that standard approaches are required to translate relative sea level information into the forms required to inform the wide range of relevant decisions across coastal management, including coastal adaptation.

The Impact of Uncertainties in Ice Sheet Dynamics on Sea-Level Allowances at Tide Gauge Locations - Aimée Slangen; Roderik Van de Wal; Thomas Reerink; Renske De Winter; John Hunter; Philip Woodworth; Tamsin Edwards (Journal of Marine Science and Engineering, 2017)
Sea level is projected to rise in the coming centuries as a result of a changing climate. One of the major uncertainties is the projected contribution of the ice sheets in Greenland and Antarctica to sea-level rise (SLR). Here, we study the impact of different shapes of uncertainty distributions of the ice sheets on so-called sea-level allowances. An allowance indicates the height a coastal structure needs to be elevated to keep the same frequency and likelihood of sea-level extremes under a projected amount of mean SLR. Allowances are always larger than the projected SLR. Their magnitude depends on several factors, such as projection uncertainty and the typical variability of the extreme events at a location. Our results show that allowances increase significantly for ice sheet dynamics’ uncertainty distributions that are more skewed (more than twice, compared to Gaussian uncertainty distributions), due to the increased probability of a much larger ice sheet contribution to SLR. The allowances are largest in regions where a relatively small observed variability in the extremes is paired with relatively large magnitude and/or large uncertainty in the projected SLR, typically around the equator. Under the RCP8.5 (Representative Concentration Pathway) projections of SLR, the likelihood of extremes increases more than a factor 10 4 at more than 50–87% of the tide gauges.

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Response to commentary by J. L. Bamber, W. P. Aspinall and R. M. Cooke (2016) - Hylke de Vries; Roderik S. W. van de Wal (Climatic Change, 2016)

How to interpret expert judgment assessments of 21st century sea-level rise - Hylke de Vries; Roderik S. W. van de Wal (Climatic Change, 2015)

Greenland’s contribution to global sea-level rise by the end of the 21st century - Rune G. Graversen; Sybren Drijfhout; Wilco Hazeleger; Roderik van de Wal; Richard Bintanja; Michiel Helsen (Climate Dynamics, 2011)

Sensible heat exchange at the Antarctic snow surface: a study with automatic weather stations - Michiel van den Broeke; Dirk van As; Carleen Reijmer; Roderik van de Wal (International Journal of Climatology, 2005)
Data of four automatic weather stations (AWSs) are used to calculate the turbulent exchange of sensible heat at the Antarctic snow surface for a 4 year period (1998–2001). The AWSs are situated on the ice shelf, in the coastal/inland katabatic wind zone and on the interior plateau in Dronning Maud Land, East Antarctica. Sensible heat flux (SHF) is calculated using the aerodynamic ‘bulk’ method between a single AWS sensor level and the surface, in combination with surface temperature derived from upwelling longwave radiation and surface roughness derived from eddy correlation measurements. Good agreement is found between calculated and directly measured SHF. All AWS sites show a downward‐directed average sensible heat transport, but otherwise the differences between the various zones are large. The surface roughness for momentum differs by an order of magnitude between the interior plateau (0.02 mm) and the katabatic wind zone (0.16 mm). On the ice shelf, frequent clouds limit surface cooling, and annual mean SHF is small (8 W m −2 ). In contrast, clear skies prevail on the interior plateau, but weak winds, an aerodynamically smooth surface and stability effects limit annual mean SHF to an equally low value (8 W m −2 ). The most favourable conditions for sensible heat exchange are found in the katabatic wind zone, where a combination of strong winds, relatively little cloud cover and a rougher surface results in annual mean SHF values of 22 to 24 W m −2 . Copyright © 2005 Royal Meteorological Society

The Summer Surface Energy Balance of the High Antarctic Plateau - Dirk van As; Michiel van den Broeke; Carleen Reijmer; Roderik van de Wal (Boundary-Layer Meteorology, 2005)

A new method to estimate ice age temperatures - Richard Bintanja; Roderik S. W. van de Wal; Johannes Oerlemans (Climate Dynamics, 2005)